Usefulness of left atrial strain for predicting incident atrial fibrillation and ischaemic stroke in the general population. (11th November 2020) - Alhakak, Alia Saed; Biering-Sørensen, Sofie Reumert; Møgelvang, Rasmus; Modin, Daniel; Jensen, Gorm Boje; Schnohr, Peter; Iversen, Allan Zeeberg; Svendsen, Jesper Hastrup; Jespersen, Thomas; Gislason, Gunnar; Biering-Sørensen, Tor
Abstract: Aims: Left atrial enlargement predicts incident atrial fibrillation (AF). However, the prognostic value of peak atrial longitudinal strain (PALS) for predicting incident AF in participants from the general population is currently unknown. Our aim was to investigate if PALS can be used to predict AF and ischaemic stroke in the general population. Methods and results: A total of 400 participants from the general population underwent a health examination, including two-dimensional speckle tracking echocardiography of the left atrium. The primary endpoint was incident AF at follow-up. All participants with known AF and prior stroke at baseline were excluded ( n  = 54). The secondary endpoint consisted of the composite of AF and ischaemic stroke. During a median follow-up of 16 years, 36 participants (9%) were diagnosed with incident AF and 30 (7%) experienced an ischaemic stroke, resulting in 66 (16%) experiencing the composite outcome. PALS was a univariable predictor of AF [per 5% decrease: hazard ratio (HR) 1.42; 95% confidence interval (CI) (1.19–1.69), P  < 0.001]. However, the prognostic value of PALS was modified by age ( P  = 0.002 for interaction). After multivariable adjustment PALS predicted AF in participants aged <65 years [per 5% decrease: HR 1.46; 95% CI (1.06–2.02), P  = 0.021]. In contrast, PALS did not predict AF in participants aged ≥65 years after multivariable adjustment [per 5% decrease: HR 1.05; 95% CI (0.81–1.35), P  = 0.72]. PALS also predicted the secondary endpoint in participants aged <65 years and the association remained significant after multivariable adjustment. Conclusion: In a low-risk general population, PALS provides novel prognostic information on the long-term risk of AF and ischaemic stroke in participants aged <65 years.